Critical notes on Plato's Politeia - Slings, S. R. (Mnemosyne, Supplements, 2005)
This volume is intended to accompany the new Oxford edition of Plato's Republic , published in 2003. It is based on a series of ten articles in Mnemosyne , dating from 1988 to 2003. It contains discussions of textual problems of various kinds. Much attention is paid to Plato's use of particles, to the moods and tenses of the verb, and to pragmatics and style. Moreover, the transmission of the text receives ample attention. The book is highly recommended for users of the new edition of the Republic , for those interested in the transmission of the Platonic corpus and in Platonic Greek and for students of linguistics in general.